Determinants of Occupational Injury: A Case Control Study among Textile Factory Workers in Amhara Regional State, Ethiopia - Zewdie Aderaw; Dagnew Engdaw; Takele Tadesse (Journal of Tropical Medicine)
Background. Occupational injuries pose major public health and socioeconomic developmental problems. However, efforts towards investigation of determinants among factory workers are very minimal in developing countries. Thus, this study aimed at to identify determinants of occupational injury among textile factory workers in Amahara regional state in Ethiopia. Methods. A case control study was done among 456 textile factory workers (152 cases and 304 controls). Self-reported data from workers and document review from factories clinics were used to ascertain occupational injury status within one-year period. Data was collected using pretested and structured questionnaire by trained data collectors. Odds ratio with 95% confidence interval was used to assess level significance. Results. Young age (<30 years) (AOR 1.90, 95% CI (1.22, 2.94)), male gender (AOR 2.54, 95% CI (1.58, 4.07)), health and safety training (AOR 1.85, 95% CI (1.17, 2.91)), sleeping disturbance (AOR 1.99, 95% CI (1.30, 3.04)), and job stress (AOR 2.25, 95% CI (1.15, 4.41)) were significant predictors of occupation injury. Conclusion. Lack of training, sleeping disturbance, and job stress increased the risk of occupational injury. So, providing basic health and safety training with special emphasis on younger and male workers, reducing stressors, and providing sleep health education were recommended.